2016
DOI: 10.3390/rs8121001
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Sensors as a Management Tool to Prevent the Invasion of the Exotic Cordgrass Spartina densiflora in the Doñana Wetlands

Abstract: Abstract:We test the use of hyperspectral sensors for the early detection of the invasive denseflowered cordgrass (Spartina densiflora Brongn.) in the Guadalquivir River marshes, Southwestern Spain. We flew in tandem a CASI-1500 (368-1052 nm) and an AHS (430-13,000 nm) airborne sensors in an area with presence of S. densiflora. We simplified the processing of hyperspectral data (no atmospheric correction and no data-reduction techniques) to test if these treatments were necessary for accurate S. densiflora det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Satellite and aerial photographs remote sensing come with numerous advantages such as revisiting a particular geographic area or place of interest on a regular cycle, which aids in facilitating data acquisition to reveal changing conditions over time (Randall, 2012). Thus, it allows understanding vegetation patterns and environmental changes of our terrestrial environment (Harvey & Hill, 2001), landscape conditions, and identifying the major causes of environmental degradation of coastal wetlands (Bustamante et al, 2016;Kirwan, 2013;Lee, 2006;Tangao et al, 2019). Remote sensing helps in substantial or regional-scale research, hard to carry out by modeling or field observations (Venevsky, 2019).…”
Section: By the International Union For Conversation Ofmentioning
confidence: 99%
“…Satellite and aerial photographs remote sensing come with numerous advantages such as revisiting a particular geographic area or place of interest on a regular cycle, which aids in facilitating data acquisition to reveal changing conditions over time (Randall, 2012). Thus, it allows understanding vegetation patterns and environmental changes of our terrestrial environment (Harvey & Hill, 2001), landscape conditions, and identifying the major causes of environmental degradation of coastal wetlands (Bustamante et al, 2016;Kirwan, 2013;Lee, 2006;Tangao et al, 2019). Remote sensing helps in substantial or regional-scale research, hard to carry out by modeling or field observations (Venevsky, 2019).…”
Section: By the International Union For Conversation Ofmentioning
confidence: 99%
“…Several studies fostered hyperspectral data with their continuous spectral band configuration, which provide more details on the spectral characteristics of plants than multispectral imagery [19]. For example, the Compact Airborne Spectrographic Imager (CASI)-1500 and the Airborne Hyperspectral Scanner (AHS) sensors, used to identify the invasive plant Spartina densiflora in a wetland, showed promising results using four spectral target detection algorithms [20]. The hyperspectral imagery of the Airborne Visible/Infrared Imaging Spectrometer (AVIRIS) was found to be capable of mapping invasive plants distributed over large areas with high overall accuracy [21], although another study suggested that AVIRIS data were not appropriate to map small and highly heterogeneous areas comprised of invasive plants due to the inadequate spatial resolution [22].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the resulting distribution maps have been used to target the management of early infestations [19,20], find the optimal time periods to apply the mitigation treatments [21], model the future invasion risk [12,19,22] or monitor the effectiveness of the management actions [23]. Most works use just spectral information from the sensors to identify the invasive plants [20][21][22][23][24][25][26][27][28][29], although some studies have found that differences in texture and phenology are also effective for their detection [12,19,27,30], as well as the fusion with non-optical data, like LiDAR (Light Detection And Ranging) point clouds [19,26,31].…”
Section: Introductionmentioning
confidence: 99%